The Role Of Organizational Support, Payroll System And Work Motivation in Improving Teachers' Job Satisfaction: A Systematic Literature Review - Zahrah; Yulia Putri Ayu Anggraini; Rida; Miftahul Aulia; Dina Hermina (PT. Hasba Edukasi Mandiri, 2025)
This article presents a systematic review of the role of organizational support, payroll systems, and job motivation in improving teacher job satisfaction. By collecting and analyzing various previous studies, this study identified a significant relationship between these three factors and job satisfaction. This research uses the literature review method to collect and analyze various relevant academic sources, namely literature studies by collecting data from journals, books, articles, and certain other writings. Then using a qualitative descriptive research method with the Systematic Literature Review (SLR) model, which is a systematic and structured approach to identify, evaluate, and synthesize all relevant evidence related to organizational support that has a significant effect on teacher job satisfaction. The results showed that strong organizational support was shown to increase teachers' sense of engagement and commitment, while a fair and transparent pay system contributed to intrinsic motivation. Additionally, high work motivation plays an important role in creating a positive work environment, which in turn increases overall job satisfaction. These findings provide valuable insights for education policymakers and school leaders in designing effective strategies to improve teacher welfare and performance.